A comment on diffusion and the displacement of atoms in metamorphic transformations. (16th September 2014) - Kretz, R.
Abstract Experimental data on diffusion in olivine <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ck14km9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Mg, Fe2SiO4</alternatives>, are used to define certain terms – diffusion coefficient, jump frequency, characteristic distance, random walk – that are useful in a discussion of atom displacements under natural conditions. Examples of atom displacements in two metamorphic terranes of the Canadian Precambrian Shield are then examined, as follows. (i) In a high‐grade metamorphic terrane in the Mid‐Proterozoic Grenville Province (Otter Lake Area), Mg concentration gradients about dolomite microcrystals in calcite and Na gradients about albite microcrystals in K‐feldspar are viewed as stranded Mg–Ca and Na–K interdiffusion gradients, formed by exsolution during slow cooling from ~700 to ~400 °C. (ii) In the Archean Slave Province (Yellowknife area), the crystallization of sillimanite, near andalusite but within crystals of quartz, possibly occurred by coupled Al–Si and oxygen–vacancy interdiffusion in quartz at ~550 °C. And the crystallization of garnet from chlorite occurred by the two‐way crystal‐boundary diffusion of several kinds of atoms across distances ranging to 3 mm. (iii) In the Otter Lake area, the crystallization of orthopyroxene–hornblende–spinel reaction zones at boundaries between crystals of olivine and plagioclase in metagabbro, evidently occurred by the mechanism of interstitial diffusion, that transported Mg, Fe, Mn and O atoms across the reaction zone from olivine to the plagioclase–(hornblende+spinel) boundary, and Si, Al, Ca and Na atoms from plagioclase to the olivine–orthopyroxene boundary, accompanied by NaSi–CaAl interdiffusion in plagioclase, and the addition of hydrogen and minor Ti, Zn, F, Cl and K from beyond the reaction zone. Also, centimetric reaction zones, with abundant biotite and plagioclase, at boundaries between K‐feldspar gneiss and deformed amphibolite dykes, evidently formed by the reaction, strained hornblende (in amphibolite) + K‐feldspar (in gneiss)→biotite (in amphibolite) + plagioclase (in gneiss), with crystal‐boundary diffusion of (Na + Ca) atoms and of K atoms across the reaction zone.